Spectral analysis of Uranus' 2014 bright storm with VLT/SINFONI - Irwin, P; Fletcher, L; Read, P; Tice, D; de Pater, I; Orton, G; Teanby, N; Davis, G (Elsevier, 2015)
An extremely bright storm system observed in Uranus' atmosphere by amateur observers in September 2014 triggered an international campaign to observe this feature with many telescopes across the world. Observations of the storm system in the near infrared were acquired in October and November 2014 with SINFONI on ESO's Very Large Telescope (VLT) in Chile. SINFONI is an Integral Field Unit spectrometer returning 64. ×. 64 pixel images with 2048 wavelengths and uses adaptive optics. Image cubes in the H-band (1.43-1.87. μm) were obtained at spatial resolutions of ~0.1″ per pixel. The observations show that the centre of the storm feature shifts markedly with increasing altitude, moving in the retrograde direction and slightly poleward with increasing altitude. We also see a faint 'tail' of more reflective material to the immediate south of the storm, which again trails in the retrograde direction. The observed spectra were analysed with the radiative transfer and retrieval code, NEMESIS (Irwin et al. [2008]. J. Quant. Spec. Radiat. Transfer, 109, 1136-1150). We find that the storm is well-modelled using either two main cloud layers of a 5-layer aerosol model based on Sromovsky et al. (Sromovsky et al. [2011]. Icarus, 215, 292-312) or by the simpler two-cloud-layer model of Tice et al. (Tice et al. [2013]. Icarus, 223, 684-698). The deep component appears to be due to a brightening (i.e. an increase in reflectivity) and increase in altitude of the main tropospheric cloud deck at 2-3. bars for both models, while the upper component of the feature was modelled as being due to either a thickening of the tropospheric haze of the 2-layer model or a vertical extension of the upper tropospheric cloud of the 5-layer model, assumed to be composed of methane ice and based at the methane condensation level of our assumed vertical temperature and abundance profile at 1.23. bar. We also found this methane ice cloud to be responsible for the faint 'tail' seen to the feature's south and the brighter polar 'hood' seen in all observations polewards of ~45°N for the 5-layer model. During the twelve days between our sets of observations the higher-altitude component of the feature was observed to have brightened significantly and extended to even higher altitudes, while the deeper component faded.